2021
DOI: 10.1088/1755-1315/890/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of nutrients in Maumere Bay, East Nusa Tenggara

Abstract: The availability of nutrients in the marine environment is very important for primary production and as indicator of the health condition in waters. East Nusa Tenggara Province is one of the province that has a potential fishery, especially in Maumere Bay of Sikka Regency. Therefore, it is necessary to monitor the water quality and spatial distribution of nutrients in that area. This study aims to determine water quality, assess water trophic status, and determine limiting factors in Maumere Bay. Sampling was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Comparison in DSi concentration in estuarine and coastal waters around the world Table 2 showed the DSi concentrations in SDB with those in comparable semi-enclosed bays in China and other countries. The results showed that the average DSi concentrations in SDB were 41.74 ± 40.48 mmol/L, which only lower than The western Bohai Bay (Wang et al, 2020), and much higher than those in Coastal waters of the northern Yellow Sea, Hangzhou Bay, Maumere Bay, and other estuaries and bays affected by human production and life (Gao et al, 2011;Zhang et al, 2020c;Meirinawati and Prayitno, 2021;Sun et al, 2022). In contrast, the mean DSi concentration in Maumere Bay was significantly lower than in other coastal waters with potential fishery resources (Meirinawati and Prayitno, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison in DSi concentration in estuarine and coastal waters around the world Table 2 showed the DSi concentrations in SDB with those in comparable semi-enclosed bays in China and other countries. The results showed that the average DSi concentrations in SDB were 41.74 ± 40.48 mmol/L, which only lower than The western Bohai Bay (Wang et al, 2020), and much higher than those in Coastal waters of the northern Yellow Sea, Hangzhou Bay, Maumere Bay, and other estuaries and bays affected by human production and life (Gao et al, 2011;Zhang et al, 2020c;Meirinawati and Prayitno, 2021;Sun et al, 2022). In contrast, the mean DSi concentration in Maumere Bay was significantly lower than in other coastal waters with potential fishery resources (Meirinawati and Prayitno, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the average DSi concentrations in SDB were 41.74 ± 40.48 mmol/L, which only lower than The western Bohai Bay (Wang et al, 2020), and much higher than those in Coastal waters of the northern Yellow Sea, Hangzhou Bay, Maumere Bay, and other estuaries and bays affected by human production and life (Gao et al, 2011;Zhang et al, 2020c;Meirinawati and Prayitno, 2021;Sun et al, 2022). In contrast, the mean DSi concentration in Maumere Bay was significantly lower than in other coastal waters with potential fishery resources (Meirinawati and Prayitno, 2021). In comparison, DSi concentrations were found to be relatively high in bays with aquaculture areas (Gao et al, 2011;Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%